Intramuscular iron-dextran and susceptibility of neonates to bacterial infections. In vitro studies. Issue 10 (October 1977) - Becroft, D M; Dix, M R; Farmer, K
Abstract : An increased incidence of E. coli sepsis has been observed in neonates given intramuscular iron-dextran for prevention of iron deficiency. Mechanisms for this apparent effect on susceptibility to infection were investigated by comparing phagocytic and antibacterial functions in paired samples of venous blood from 7 infants, median age 5 days, before and after iron-dextran. Post-treatment sera had increased inhibitory effects on leucocyte chemotaxis and markedly reduced bacteriostatic effects agaainst E. coli. The clinical relevance of the effects on chemotaxis is uncertain. The reduction in serum bacteriostasis is similar to that observed in other forms of hyperferraemia not associated with saturation of transferrin, and is a likely cause of the increased susceptibility to infection in vivo. We consider that prophylactic treatment with parenteral iron-dextran is contraindicated in early infancy.